Modular transportation system with a three dimensional routeing - Löffler Christoph; Canders Wolf-Rüdiger (Archives of Electrical Engineering, 2015)
In intra-enterprise logistics and automation of manufacturing processes general a rising productivity by high flexibility is required. Existing transportation systems exclusively use two-dimensional track sections, because they can be served with standard drives. Because of these simple structures the transport speed is limited and thereby also the throughput. In this paper now a modular transportation system is presented which could reach higher speeds with a direct drive and the use of centrifugal force compensating curves. Simultaneously the system also can change the altitude. All this succeeds with the integration of three-dimensional track sections. Therefore a two piped guiding system with a long stator linear motor was designed. To combine the linear motor with the three dimensional track special stator elements were developed which allow a bending of the stator to follow the route course. The current work deals with the implementation of a mechanical passive switch, which is operated by the electromagnetic forces of the linear motor. So no additional mechanical actors or a separate electromagnetic system are necessary.